EDUKASI PENCEGAHAN JEBAKAN PINJAMAN ONLINE ILEGAL KEPADA WARGA TAMBAK BOYO RAYA - Wahyu Puspitasari; Rusdiana Permanasari; Linda Novasari; Khoiriana Nur Hani’ah; Mutiara Nur Haliza (Jurnal Abdimas Bina Bangsa, 2024)
The development of digital technology in Indonesia occurs every year, as well as the development of information and communication technology has opened up new opportunities in the financial world. With the advancement of digital technology, there have been many changes in all sectors in companies and other institutions, changes in sectors that have undergone changes, one of which is the financial sector with the emergence of Financial Technology (Fintech) or known as financial technology that has just been pioneered, one example is Online Loans. The presence of this Online Loan in addition to having positive benefits but we must not be careless regarding the negative impact, if you use an online loan application, because in the fintech finance business application, many illegal online loans are found that are not registered with the Financial Services Authority (OJK). These illegal online loans often have unethical collection practices and are detrimental to borrowers, therefore we are urged to be smarter regarding their use. Like the phenomenon of cases that occurred, it is worth seeking the truth and the right solution experienced by the residents of Tambak Boyo Raya, they do not use the application, but the majority of them get bills related to online loans. Our PKM activities use qualitative research methods, using case study methods, and using a work shop or talk-show approach, primary data, using comprehensive stages such as thorough observation, structured and in-depth interviews using pre-test and post-test questions related to PKM topics, and activity documentation in the form of activity photos, implementation videos, and mass media news. This PKM activity was held at the Banyu Mili Tambak Boyo Raya Multipurpose Building, Semarang City, attended by 70 participants from the Tambak Boyo Raya community, the resource person was the Head of the Public Service Education Sub-Division who provided interesting material, Guest Star who came from a Senior Lecturer at the Faculty of Economics, University of Semarang. The results of the Community Service Activities obtained, namely our activities were successful and went well, the enthusiasm of the participants who attended with a positive response, the material discussed by the resource persons was very good and interesting